Principal Leadership on Special Education Implementation: Basis for a Development Program - Casaul, Ralph L.; Tumolva, Princess Jemma B.; Payos, Angelica D. (Future Science / FSH-PH Publications, 2025)
During S.Y. 2024–2025, this study looked at how school principals in the Division of Cavite, implemented special education (SPED) programs. A questionnaire created by the researcher was used to collect data from 120 school principals using a descriptive-quantitative design. The results showed that principals were very involved in advocacy (4.59), including students with disabilities in decision-making (4.78), and keeping an eye on inclusive practices (4.53). However, stakeholder engagement (2.85) and staff professional development (2.64) received lower ratings. Stakeholder engagement (2.46) and innovation (2.81) trailed behind integrity (4.88), motivation (4.82), and feedback (4.72), which were all highly correlated with leadership behaviors. Keeping up with technology (4.85), scarce resources (4.79), and resolving conflicts (4.76) were the main obstacles. Principals' engagement and leadership behaviors were found to be significantly positively correlated (r = 0.819, p <.001). In order to improve inclusive education outcomes, a development program that emphasizes leadership training, resource management, teamwork, staff professional development, and parent-community partnerships was suggested in light of these findings.